European lessons from Silicon Valley Bank resolution: A plea for a comprehensive demand deposit protection scheme (CDDPS) - Florian Heider; Jan Pieter Krahnen; Loriana Pelizzon; Jonas Schlegel; Tobias Tröger (Leibniz Institute for Financial Research SAFE, 2023)
The SVB case is a wake-up call for Europe's regulators as it demonstrates the destructive power of a bank-run: it undermines the role of loss absorbing capital, elbowing governments to bailout affected banks. Many types of bank management weaknesses, like excessive duration risk, may raise concerns of bank losses - but to serve as a run-trigger, there needs to be a large enough group of bank depositors that fails to be fully covered by a deposit insurance scheme. Latent run-risk is the root cause of inefficient liquidations, and we argue that a run on SVB assets could have been avoided altogether by a more thoughtful deposit insurance scheme, sharply distinguishing between loss absorbing capital (equity plus bail-in debt) and other liabilities which are deemed not to be bail-inable, namely demand deposits. These evidence-based insights have direct implications for Europe's banking regulation, suggesting a minimum and a maximum for a banks' loss absorption capacity.
urn:nbn:de:hebis:30:3-640587
Keywords: 330; European Deposit protection scheme